Implementation of Swimming Class Booking Management System with Role-Based Access Control (RBAC) and Multi-Factor Authentication (MFA) For M&M Swimming Club - Hasnan, Nur Iman Sabreena; Harun, Nur Ziadah (Applied Information Technology And Computer Science, 2026)
In this era of technology, a web-based booking management system for classes or facilities has broadly been used by many sport clubs because it provides flexibility and adaptability to users. The paper-based method used by the M&M for administrative tasks, causes higher risk for data loss along with less flexibility for data resources. Additionally, there were concerns regarding adapting into new technology due to the complexity of the technology. Along with that, it is important to implement security mechanisms such as Role-Based Access Control (RBAC) and Multi-Factor Authentication (MFA) to protect sensitive data. Therefore, this project will develop a web-based swimming class booking system along with the implementation of MFA and RBAC to ensure data protection against threat actors. The result of this project will produce a well-designed interface along with supportive resources will assist the users in adapting to the system.